The role of the nurse in thrombolytic therapy for patients with an acute ischaemic stroke - Jaracz, Krystyna (Pielęgniarstwo Chirurgiczne i Angiologiczne/Surgical and Vascular Nursing, 2009)
Contemporary rules of organization of treatment in the acute phase of ischaemic stroke have lessened the risk of death and severe long-term neurological deficits in patients. The modern-day treatment for an acute stroke involves medicine which restores blood flow in the occluded brain vessels (rt-PA). To be effective and relatively safe, this kind of treatment must be given immediately, i.e. within 3 hours after symptoms begin, and the management protocol must be strictly followed by the medical staff. The role of the clinical nurse is crucial in this service. This role includes organization and coordination of diagnostic procedures, an early assessment and continuous monitoring of basic vital and clinical signs, as well as provision of acute nursing stroke care.